2015
DOI: 10.5301/uro.5000120
|View full text |Cite
|
Sign up to set email alerts
|

Onabotulinumtoxina Intravesical Treatment in Patients Affected by Overactive Bladder Syndrome: Best Practice in Real-Life Management

Abstract: Purpose:We evaluated intradetrusorial OnabotulinumtoxinA (Onabot/A) treatment protocols in patients with idiopathic overactive bladder (OAB), in order to assess the care of patients before, during and after treatment. Methods: In 64 OAB patients injected with Onabot/A, we reviewed the length of the hospital stay, frequency of catheterization, frequency of intraoperative and postoperative complications, and patients' satisfaction to the proposed treatment protocol (as assessed by VAS). We also compared the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We chose a daysurgery protocol because it affords greater safety to clinicians if complications arise that require management; however, other authors reported successfully applying treatment in outpatient settings. 28 Despite reports in the literature of a non-negligible discontinuation rate (between 10% and 30%), 29 none of the patients in our series abandoned the study. In other papers, the most commonly cited reasons for discontinuing treatment were lack of efficacy or dislike of CIC; 30 however, we did not record any occurrences of inability to perform CIC or of pain on injection.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We chose a daysurgery protocol because it affords greater safety to clinicians if complications arise that require management; however, other authors reported successfully applying treatment in outpatient settings. 28 Despite reports in the literature of a non-negligible discontinuation rate (between 10% and 30%), 29 none of the patients in our series abandoned the study. In other papers, the most commonly cited reasons for discontinuing treatment were lack of efficacy or dislike of CIC; 30 however, we did not record any occurrences of inability to perform CIC or of pain on injection.…”
Section: Discussionmentioning
confidence: 65%
“…We chose a day-surgery protocol because it affords greater safety to clinicians if complications arise that require management; however, other authors reported successfully applying treatment in outpatient settings. 28…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at first injection was 60.7 ± 15.3 years . Globally, 268 treatments were performed and the mean number of injections per patient was 1.96 ± 1.32 (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
“…Although urgency UI may suggest detrusor overactivity, it is not necessary to urodynami-cally demonstrate involuntary contractions of the muscle 5 . OAB is coined as idiopathic (iOAB) when a specific metabolic or pathologic condition that can be the cause is not identified 3 …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the first line treatment for OABS relies on the application of antimuscarinic drugs (Madhuvrata et al, 2012 ; Veenboer and Bosch, 2014 ). The second line therapies include botulinum toxin injection into the detrusor muscle (Chapple et al, 2013 ; Nitti et al, 2013 ; Mangera et al, 2014 ; Giannantoni et al, 2015 ), sacral neuromodulation (Peters et al, 2009 , 2010 ; Sukhu et al, 2016 ) or invasive surgical interventions such as an augmentation cystoplasty (Reyblat and Ginsberg, 2008 ). However, these therapeutic interventions are only effective in a subset of patients and their effectiveness is limited in the remainder.…”
Section: Introductionmentioning
confidence: 99%